Strategi Komunikasi Kesehatan Dalam Percepatan Penurunan Kondisi Stunting Pada Anak Di Lubuk Pakam Deli Serdang - Muhammad Rizki Irwan; Faustyna Faustyna (Universitas Muhammadiyah Sumatera Utara, 2023)
Health Communication is a communication that plays a very important role in the success of several programs and so on, especially in reducing stunting conditions. Given that stunting is a government program that must be implemented by all health agencies without exception. To realize the reduction in stunting conditions, the government, especially puskesmas must take part in this program in order to reduce stunting conditions. The purpose of this study was to determine the health communication strategy carried out by the puskesmas to the community. The theory used is health communication, interpersonal communication, and stunting. While the research method used in this study is a qualitative descriptive approach. There are two ways to collect data, namely in-depth interviews and documentation. The data analysis technique is qualitative by observing and interviewing. From the results of the study it can be concluded that the role of the puskesmas is needed to make the program a success and also health communication between the puskesmas and the community runs very well and smoothly. In addition, through conversations, dialogues, and sharing experiences, it is one of the important aspects of communication carried out by the puskesmas to the community.